2020
DOI: 10.29252/ibj.24.5.283
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDAC8 Expression with Pathological Findings in Triple Negative and Non-Triple Negative Breast Cancer: Implications for Diagnosis

Abstract: Background: Previous data have shown the tumorigenicity roles of HDAC8 in breast cancer. More recently, the oncogenic effects of this molecule have been revealed in TNBC. The present study aimed to determine the diagnostic value of HDAC8 for the differentiation of TNBC from nTNBC tumors. Methods: A total of 50 cancerous and normal adjacent tumor specimens were obtained, and the clinical and pathological findings of studied subjects were recorded. The expression of HDAC8 gene was determined by qRT-PCR. Also, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In TNBC preclinical models, both HDAC6 inhibitors YSL-109 and 10 g have exhibited significant anti-proliferative activity [ 225 , 226 ]. The overexpression of HDAC8 in TNBC is associated with TNBC tumor size, lymphatic infiltration, and tumor grade [206] . HDAC8 can activate YY1 or Hippo/YAP signaling to promote the proliferation and migration of TNBC [ 227 , 228 ].…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%
See 2 more Smart Citations
“…In TNBC preclinical models, both HDAC6 inhibitors YSL-109 and 10 g have exhibited significant anti-proliferative activity [ 225 , 226 ]. The overexpression of HDAC8 in TNBC is associated with TNBC tumor size, lymphatic infiltration, and tumor grade [206] . HDAC8 can activate YY1 or Hippo/YAP signaling to promote the proliferation and migration of TNBC [ 227 , 228 ].…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%
“…The dynamic equilibrium between HDAC and histone acetylase (HAT) intricately governs chromosome modification and gene expression. Perturbations in this balance, characterized by heightened histone deacetylation and diminished acetylation, can induce aberrations in the cell cycle, thereby fostering tumorigenesis [206] . Studies have shown that histone differences are associated with TNBC [206] .…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC8 was found to be overexpressed in OSCC tissues, and HDAC8 silencing significantly inhibited the proliferation of OSCC cells by the induction of apoptosis through caspases activation and pro-survival autophagy ( Ahn and Yoon, 2017 ). In breast cancer tissue, there was a significant association between HDAC8 overexpression and perineural invasion ( p < 0.05) ( Menbari et al, 2020 ).…”
Section: Specific Epigenetic Modifications In Head and Neck Squamous ...mentioning
confidence: 99%
“…HDAC8 was demonstrated to form complex with SMAD3/4 and transcriptionally suppresses SIRT7 thereby reduce metastasis and increase chemotherapy efficacy in breast cancer (Tang et al, 2020). Meanwhile, the expression of HDAC8 is related to the pathological results in triple-negative breast cancer (TNBC), which indicated the potential in the diagnosis of TNBC tumors (Menbari et al, 2020). HDAC class III sirtuins are found to be overexpressed in breast cancer.…”
Section: Insight Into the Histone Acetylationmentioning
confidence: 99%